Mathematical Modelling of Bio-oil/Char Slurry Steam Gasification in a Fluidized Bed Reactor - Hassani Ghezelchi, Mansoor (Curtin University, 2018)
This PhD study focuses on gasification of bio-oil/bioslurry in fluidized bed reactor. A methodology was developed for quantifying droplet size distribution from the atomisation of bio-oil or bioslurry. Spray characteristics were then reported for two fast pyrolysis bio-oils and a set of bioslurry samples with different atomizers. Mathematical modelling was then carried out to investigating syngas production from bio-oil/bioslurry gasification, taking into consideration the effect of operating conditions (e.g. droplet size) on syngas production.